Biolarvacidal activity of methanol extract of Kipahit leaves (Tithonia diversifolia) against larvae of Chrysomya bezziana fly - Wardhana AH; Diana N (Jurnal Ilmu Ternak dan Veteriner, 2014)
Myiasis or “belatungan” is the infestation of live human and vertebrate animal tissue with dipterous larvae, Chrysomya bezziana. In general, synthetic insecticides were applied to control the disease. However, it causes negative impact on animal product, so that it is required to find an alternative treatment using herbal medicine. The aim of this study was to access activity of methanol extract of Kipahit leaves (Tithonia diversifolia) against various stages of C. bezziana larvae (L1, L2 and L3). Five treatments were applied with five replications, i.e. control/water (P0), 0,5%, 1%, 2% of the extract for PI, PII and PIII, respectively. Another treatment was 0,05% Asuntol for positive control (PIV). Each treatment was added with1% DMSO and twenty larvae were examined for each replication. Bioassay of L1 and L2 was addressed to investigate effect of intestinal toxicity by mixing the extract with Meat-Blood Mixture (MBM) and Larval Rearing Media (LRM) for L1 and L2, respectively. Bioassay of L3 was to investigate effect of contact toxicity through soaking the larvae into the extract solution for 10 seconds followed by incubating in vermiculite at 36oC. All living larvae after being treated by various concentration of the extract were reared to pupae and allowed to emerge as imago. Number of living larvae and pupae, pupae weight and number of imago were observed. All data were analysed using ANOVA followed by Dunnett test at 95% confidential limit. For L2, larval mortality were counted and probit analysed using POLO-PC software, therefore the lethal concentration (LC50 and LC95) and lethal time (LT50 and LT95) were defined. Results demonstrated that 1% of the extract was the most effective concentration which was able to kill the larvae and decrease the pupae weight. It also caused to fail pupation and imago emergence. The further study might be pursued to investigate in vivo assay of the extract in infested livestock. Key Words: Tithonia diversifolia, Myiasis, Chrysomya bezziana, Biolarvasidal